Optimal Methionine + Cysteine / Lysine Ratio for First Cycle Phase 1 Commercial Leghorns - Bateman, Andrew; Roland, Sr., D.A.; Bryant, M. (International Journal of Poultry Science, 2008)
A study was conducted to determine the optimal methionine plus cysteine to lysine (Met+Cys/Lys) ratio in corn-soy diets of Hy-Line W-36 hens (wk 21-34) during Phase 1. Hens (n = 1,920; 21-wk old) were randomly divided into 12 groups of 160 hens per group (20 hens x 8 replicates for each treatment). Three levels of lysine (0.79, 0.87 and 0.97%) with four Met+Cys/Lys ratios (0.71, 0.75, 0.79 and 0.83) were used. Response criteria were egg production, feed consumption and egg weight. An interaction (P < 0.001) was observed between lysine (Lys) level and Met+Cys/Lys ratio on egg production, feed consumption and egg weight. Lowering the Met+Cys/Lys ratio in the lowest Lys diet (0.79%) had an adverse effect on egg production, feed consumption and egg weight, however there was little or no effect on these parameters in diets containing two higher Lys levels (0.87 and 0.97%). An economic analysis indicated that the optimal Met+Cys/Lys ratios for diets containing 0.97, 0.87 and 0.79% lysine were 0.71, 0.75 and 0.83, respectively. Results indicated that the current National Research Council (NRC, 1994) recommendation of 0.83 for the Met+Cys/Lys ratio was too high for diets containing higher lysine or protein levels required for low consuming hens at peak production. Egg producers using a Met+Cys/Lys ratio of 0.83 may be overfeeding synthetic methionine by as much as one pound or more per ton of feed.